(untitled) (Journal of Global Arts Studies, 2025)
Background: As an essential part of traditional Chinese arts and crafts, lacquerware has been profoundly affected by industrialization and changing social lifestyles since the twentieth century. Its production mechanisms, transmission models, and aesthetic contexts have been severely disrupted, leading to challenges such as the aging of inheritors, the absence of training systems, limited market access, and declining social recognition. Objective: This study adopts a systemic construction perspective to examine the core issues in the inheritance and preservation of contemporary Chinese lacquerware craftsmanship and to explore feasible institutional strategies. Methods: The study finds that the inheritance and preservation of contemporary Chinese lacquerware craftsmanship are hindered by fragmented policy implementation, insufficient educational support, and inefficient multi-actor collaboration. Results: The inheritance and preservation of contemporary Chinese lacquerware should shift from a project-based to a platform-based model, establishing a collaborative mechanism that engages government, inheritors, educational institutions, enterprises, and the public to ensure the sustainable transmission and contemporary expression of lacquerware craftsmanship.